Relationships between level of Knowledge and Perception with Motivation for Conducting HPV Cervical Cancer Vaccination in Female Senior High School Students with HPV Cervical Cancer Vaccination Program and Non Program in Badung Regency 2014 - Swari, Ida Ayu Sinthia Pradnya; Hartanto, Rifai; Budiani, Dyah Ratna (Nexus Kedokteran Komunitas, 2014)
Backgrounds : Cervical cancer is a cancer that occurred at cervical region of female reproduction organs and occupies the top level for causing women mortality in the world compared to other type of cancer. Cervical cancer is caused by Human Papilloma Virus (HPV) infection. HPV cervical cancer vaccination is one method to decrease cervical cancer occurrence. Good knowledge and perception are supposed to arise high motivation in conducting HPV cervical cancer vaccination. This research aims to know the relationships between level of knowledge and perception with motivation to conduct HPV cervical cancer vaccination in female senior high school students with HPV cervical cancer vaccination program and non program in Badung regency 2014. Methods : This research is an analytical observation. Sample of this research are 100 female Senior High School students in Badung regency which are chosen by simple random sampling. The data are collected by questionnaire related with knowledge, perception, and motivation, then analyzed with Double Logistic Regression. Results : This research results show that knowledge has significant positive relationship with motivation to conduct HPV cervical cancer vaccination (p = 0.001 CI 95% = 2.123-22.412). Perception also has significant positive relationship with motivation to conduct HPV cervical cancer vaccination (p = 0.011 CI 95% = 1.404-13.733). Knowledge and perception relationships with motivation to conduct HPV cervical cancer vaccination are 28.80% (Negelkerkel Rsquare = 0.288). Conclusions : There are positive relationships between level of knowledge and perception concerning motivation to conductÂ  HPV cervical cancer vaccination in female senior high school students with HPV cervical cancer vaccination program andÂ  non program in Badung regency 2014, higher level of knowledge and better perception are related with higher motivation to conduct HPV cervical cancer vaccination in female senior high school students with HPV cervical cancer vaccination program and non program in Badung regency 2014. Keywords : Cervical Cancer, HPV Cervical Cancer Vaccination, Knowledge, Perception, Motivation.Â